Effect of Buyang Huanwu Decoction Foot Bath on Pulmonary Rehabilitation of Patients with Chronic Obstructive Pulmonary Disease at Stable Phase - HUANG Huirong; HAN Xueqi; LIU Qinyu; XUE Jialu; YU Zhenling; CHEN Bin; MIAO Shaofang; CHEN Shuifeng (康复学报)
Objective: To observe the effect of Buyang Huanwu decoction foot bath on pulmonary function and quality of life of patients with chronic obstructive pulmonary disease (COPD) at stable phase, improving the clinical treatment plan for COPD patients and providing clinical evidence to promote pulmonary rehabilitation.MethodsA retrospective analysis of 60 patients with COPD at stable phase who were admitted to the Affiliated People's Hospital of Fujian University of Traditional Chinese Medicine from June 2020 to February 2021 and met the inclusion criteria of this study were divided into treatment group and control group using the SPSS 26.0, with thirty cases in each group. The control group was given routine drug treatment, nursing therapy, guided exercise, and health education. The treatment group received the Buyang Huanwu decoction foot bath in addition to the treatment of the control group. To be specific, the prepared Buyang Huanwu decoction was immersed in 5,000 mL water for twenty minutes. After boiling, the decoction was changed to simmer for ten minutes. After discarding the residue, the decoction was placed in a bucket, and foot bath was conducted when the temperature dropped to about 40 ℃. Foot bath required the water surface to be 10 cm above the ankle joint, twenty minutes per time, and once per day before going to bed, seven times per week, continuous treatment for two weeks. At both the before treatment and after treatment for two weeks, the percentage of forced expiratory volume in 1 second to predicted value (FEV1%pred) and forced expiratory volume in 1 second/forced vital capacity (FEV1/FVC) were used to evaluate the changes of pulmonary function in COPD patients at stable phase; the change of locomotor ability was observed by 6-minute walk distance (6MWD); the changes in the degree of dyspnea were assessed using the dyspnea scale of modified British Medical Research Council (mMRC); the chronic obstructive pulmonary disease assessment test (CAT) was used to observe the changes of patients' quality of life; the anxiety inventory for respiratory disease (AIR) was used to evaluate the change of anxiety. To evaluate the safety of the Buyang Huanwu decoction foot bath in treating COPD patients at stable phase, the vital signs were recorded before and after the intervention, and recording the adverse reactions during the intervention, such as palpitations, and breathing difficulties.Results1) Before treatment, there was no significant difference in FEV1%pred, FEV1/FVC value, 6MWD, mMRC score, CAT score, and AIR score between the two groups (P>0.05). 2) Compared with the situation before treatment, the FEV1%pred, FEV1/FVC value, and 6MWD of the two groups all increased (P<0.05), but the mMRC score, CAT score, and AIR score all decreased (P<0.05). After 2 weeks of treatment, the FEV1%pred, FEV1/FVC value, and 6MWD of the treatment group were all higher than those of the control group (P<0.05); the mMRC score, CAT score, and AIR score of the treatment group were all lower than those of the control group (P<0.05). 3) Safety results showed that no adverse events occurred during the clinical treatment, suggesting that the Buyang Huanwu decoction foot bath was safe and reliable.ConclusionThe Buyang Huanwu decoction foot bath could improve pulmonary function, athletic ability, dyspnea, anxiety level, and quality of life of COPD patients at stable phase. The clinical effect is good and can be promoted clinically.